Efforts of the Health Quarantine Center in Managing Port Environmental Pollution Supervision - Wulan Syafina; Nisha Desfi Arianti; Tri Mardalena (Global Insights in Management and Economic Research, 2025)
Purpose of the study: Environmental pollution in domestic port areas poses increasing risks to public health and operational sustainability. As the designated authority for port environmental health, the Health Quarantine Office (BKK) is mandated to supervise, prevent, and control potential sources of pollution. Strengthening its supervision mechanisms is essential to ensure effective environmental health management. This study aims to analyze the monitoring efforts undertaken by the Health Quarantine Office Class I Tanjung Balai Karimun in controlling environmental pollution at domestic ports and to evaluate the effectiveness of its environmental monitoring activities. Materials and methods: A descriptive qualitative research design was employed. Data were collected through field observations, in-depth interviews with BKK officers and port management personnel, and documentation review. Data analysis included data reduction, data display, and conclusion drawing to systematically describe the monitoring processes and outputs. Results: Findings indicate that BKK implements several monitoring activities, including water quality testing, ship waste management supervision, sanitation inspections of port facilities, and environmental awareness education for port users. Despite these efforts, several challenges persist, particularly limitations in human resources, laboratory infrastructure, and the consistency of monitoring schedules. Conclusions: The study highlights the essential role of BKK not only in safeguarding human health but also in mitigating environmental pollution within domestic ports. The results underscore the need for enhanced institutional capacity and integrated environmental monitoring policies to improve the effectiveness and sustainability of port environmental health management.